Cloning, sequencing and characterization of the human alpha glutathione S-transferase gene corresponding to the cDNA clone pGTH2. - Klöne, A (1992)
The human Alpha glutathione S-transferase gene corresponding to the human liver cDNA clone pGTH2 was isolated from a cosmid genome library. The gene, represented by the clone cosGTH2, spans nearly 12 kb and contains seven exons. The intron/exon borders conform to the standard rules, and an open reading frame is present, starting at position 67 in exon 2, the double-stop codon being at position 733 in exon 7. Exons 1, 2 and 7 differ in length from the known rat gene coding for the Ya enzyme. A 209 bp 5'-upstream region contains TATA and CAT boxes and, in addition, motifs for Sp1-, NF1- and HNFI-binding factors. Clone cosGTH2 represents the less basic subunit, alpha y, of two Alpha glutathione S-transferase subunits (alpha x and alpha y) expressed in liver, which is identical with the kidney subunit alpha 2.